2020
DOI: 10.1007/s42452-020-2217-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate temperature on bismuth oxide thin films grown by pulsed laser deposition

Abstract: We present and discuss on bismuth oxide films grown on cost-efficient BK7 glass slides by pulsed laser deposition using a metallic target. Our choice is of particular interest due to the high number of intermediate bismuth oxides that can form during the oxidation process, along with the polymorphs of the stoichiometric oxide, i.e. bismuth trioxide (Bi 2 O 3). We show that the oxidation degree of bismuth increases with substrate temperature, t S (300-600 °C), when grown in 100 sccm flow at 6 × 10 −1 mbar O 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
3
4
0
Order By: Relevance
“…These calculations indicated that the direct allowed bandgaps for the Bi2O3:Ho 3+ thin films were 2.89, 2.20, 2.18, 2.33, 2.36 and 2.56 eV for TS of RT, 200, 300, 400, 500 and 600 °C, respectively. These values correspond well with those reported previously [11] and with the 2.85 eV [1] that was reported the optical band gap for a 1 mol.% Bi2O3:Ho 3+ powder. The obtained optical band gap values for TS of 200 to 600 °C are relatively smaller than the previous reported values for the powder sample, and that may have been due to the high density of structural defects and presence of the hetero α-and β-phases present in the current products.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These calculations indicated that the direct allowed bandgaps for the Bi2O3:Ho 3+ thin films were 2.89, 2.20, 2.18, 2.33, 2.36 and 2.56 eV for TS of RT, 200, 300, 400, 500 and 600 °C, respectively. These values correspond well with those reported previously [11] and with the 2.85 eV [1] that was reported the optical band gap for a 1 mol.% Bi2O3:Ho 3+ powder. The obtained optical band gap values for TS of 200 to 600 °C are relatively smaller than the previous reported values for the powder sample, and that may have been due to the high density of structural defects and presence of the hetero α-and β-phases present in the current products.…”
Section: Resultssupporting
confidence: 93%
“…The obtained optical band gap values for T S of 200 to 600 • C are relatively smaller than the previous reported values for the powder sample, and that may have been due to the high density of structural defects and presence of the hetero αand β-phases present in the current products. interference [11,75]. The results in Figure 20 clearly indicate that the reflectance is dependent on the film thickness, and the highest reflectance was achieved for the films grown at the RT that coincided with the thickest film observed.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…From spectra in Fig. 2, the film thickness (d) can be calculated in each period by the following equation [25]:…”
Section: Resultsmentioning
confidence: 99%